Improvement of Mechanical Properties and Adhesion of Ti-Al-Si-N Coatings by Alloying with Ta - Artur R. Shugurov; Evgenii D. Kuzminov; Yuriy A. Garanin; Alexey V. Panin; Andrey I. Dmitriev (Lubricants, 2022)
The effect of the Ta content on the structure, mechanical properties and adhesion of magnetron-sputtered Ti1-x-y-zAlxTaySizN coatings was studied. According to the energy-dispersive X-ray spectroscopy analysis, the coatings studied had the following chemical compositions: Ti0.41Al0.49Si0.10N, Ti0.38Al0.47Ta0.05Si0.10N, Ti0.36Al0.44Ta0.10Si0.10N and Ti0.35Al0.40Ta0.15Si0.10N. The X-ray diffraction experiments revealed the B1-type fcc crystal structure of the coatings. The increasing Ta content was found to induce the texture evolution from (200) to (111), which was attributed to a significant increase in the residual compressive stress in the coatings. The hardness monotonically increased from 32.7 to 42.2 GPa with increasing the Ta content, while the reduced Young’s modulus decreased from 369 to 353 GPa. The adhesion of the coatings to the Ti substrate was evaluated by scratch testing. It was found that the Ti0.36Al0.44Ta0.10Si0.10N coating was characterized by maximum adhesion strength, while incorporation of a larger amount of Ta resulted in earlier coating spallation due to the high residual compressive stress.